Debate Estruturado: Uma Estratégia Pedagógica para Ensino e Aprendizagem de Valores Humanos em Interação Humano-Computador - Ponciano, Lesandro (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2018)
Interactive systems are increasingly present in people’s daily lives, generating new demands for interface and interaction. Examples of demands are those derived from human values, such as: gender identity, privacy, and the need for systems to provide explanations to the people who use them. Therefore, to be successful, professionals working in the area of HumanComputer Interaction (HCI) need to be increasingly sensitive to these values. Unfortunately, there are still few pedagogical resources to help HCI students develop such sensitivity. Seeking to contribute to the solution of this problem, in this work, it is proposed and analyzed the use of the pedagogical strategy denominated Structured Debate. Based on the pedagogies of active learning and collaborative learning, Structured Debate follows three phases: 1) pre-debate phase, which consists of preparing for the debate by reading reference texts; 2) execution of the debate in the classroom through a structure of questions, answers, considerations and movements in the room; and, 3) post-debate phase, when the effects of the debate are observed and contextualized in new contents of the discipline. We discuss experiences of the use of the strategy in five classes of the discipline HCI in two bachelor undergraduate courses: Information Systems and Software Engineering. The results suggest that Structured Debate stimulates and engages students with HCI topics about human values.